Kualitas Visual Fasade Bangunan Modern Pasca Kolonial di Jalan Kayutangan Malang - Fauziah, Nur; Antariksa, Antariksa; Ernawati, Jenny (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2012)
Malang is one of the cities designed by Dutch with spesific attention to the aesthetic of urban environments. Kayutangan Street is a historic street corridor which plays a prominent role on the physical development of the city of Malang. In visual architectural context, a row of building facades along the Kayutangan streetscape is the main element of visual beauty and character creation of the characteristic in the Kayutangan corridor. The aims of this research are to investigate the general public and professional in the field of architecture judgment about the role of visual elements to the appearance of modern building facades in Kayutangan corridor, as well as to find out the most influential visual element to the appearance of modern building facades at Kayutangan Street. The method used is quantitative method by the independent sample t-test, factor analysis, and multiple linear regression analysis. The results showed that both groups of respondents rating are not much different, on a range of â€œless importantâ€ to â€œimportantâ€ assessment scale. The visual components which are the most influential on modern building facades in Kayutangan Street are Geometric Component (architectural style, facade form, horizontal line, and vertical line). The next influential component is Visual Touching Effect & Color Dimension Component (texture, decorative ornament, material, facade color, saturation, brightness)Keywords: visual elements, modern building facade, Kayutangan streetscape